PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEBSITE MELALUI GOOGLE SITE UNTUK KETERAMPILAN MENULIS BAHASA JERMAN KELAS XII SMA - Yasinta Ekadina Rinfi Putri,; Fahmi Wahyuningsih, (LATERNE, 2025)
Based on the questionnaire, it is known that students have difficulties in learning German, especially in writing. Therefore, a Website-based learning media was developed through Google Site for learning German writing skills in class XII SMA. The learning media was developed as a Website made through Google Site and contains a summary of the Reisen theme material, practice questions, and an interactive quiz. The formulation of the problems in this study are, (1) How is the development of web-based learning media through Google Site for German writing skills class XII SMA. (2) How is the feasibility of Website learning media that has been developed. The objectives of this study are as follows: (1) to describe the process of developing Website-based learning media for German writing skills in grade XII high school. (2) To find out the feasibility of Website learning media that has been developed. This research is included in Research and Development (R&D) using the ADDIE development method (Analysis, design, Development, Implementation, Evaluation). This research was only carried out up to the development stage and ended with validation by experts. The results of the feasibility test from the material expert obtained a value of 90% and the media feasibility test obtained a value of 88.8%. From these results, it can be concluded that the media developed can be used to learn German.